Analisis kesulitan pembelajaran daring yang dialami guru dan peserta didik pada pelajaran tema 4 KD 3.10 di kelas III sekolah dasar - Ambar Kusuma Dewi; Rukayah Rukayah; Joko Daryanto (Universitas Sebelas Maret, 2021)
Analysys of online learning difficulties experienced by teachers and students in Indonesian Theme 4 KD 3.10 subjects in class III SD N Palur 03.The purpose of this study is to describe the difficulties of online learning experienced by teachers and students in Indonesian Language subjects Theme 4 KD 3.10. This research is a qualitative research with a qualitative descriptive method. Sources of data and data come from teachers and students. The number of research subjects was 10 students by taking samples using purposive sampling technique. Data collection techniques using interviews, questionnaires, and document study. The validity test used technical triangulation. Data analysis using interactive analysis techniques Milles and Huberman. The results showed that the difficulty of online learning experienced by teachers in the subject of Indonesian Language theme 4 KD 3.10, namely the difficulty of teachers in the preparation of subject matter, procurement of approaches and implementation of the 2013 curriculum. Meanwhile, online learning difficulties experienced by students in Indonesian theme 4 KD subjects 3.10, namely students mostly have difficulty in constructing their own knowledge and are technically constrained.